Siedem cech charakteryzujących nową ewangelizację - Zborowski, Michał (Annales Missiologici Posnanienses, 2020)
The new evangelization is a concrete task, precisely described in the documents and teaching of the Church. Its characteristic features include: a new context in which the Gospel is proclaimed, a new recipient of this message, a new enthusiasm, new methods, new means of expression, as well as a new keryx and a new content, which is the kerygma sensu stricto. The new evangelization is one of the three types of evangelization in addition to the mission ad gentes and the ordinary evangelization.